Marvel media convergence: cult following and buddy banter - Raphael, Jackie; Lam, Celia (Intellect Ltd., 2016)
The social media driven paradigm shift and convergence of mass media has transformed celebrity culture, and affected the way fans are entertained and audiences interact with celebrities and fan communities. The series Marvel’s Agents of S.H.I.E.L.D marked Marvel Studio’s first foray into the medium of television. In a convergent media environment in which content saturation is a potential barrier to audience attention and commercial success, the leveraging of celebrity friendship is an effective means of promotion. The series was launched at the 2013 Comic Con in San Diego, during which the cast participated in interviews that were distributed online. This article explores the success of celebrity friendships as a marketing device through an analysis of audience comments in response to one online interview. It examines how displays of friendship generate online discussion, audience hype and reward loyalty, and the significance of perceived authenticity on the reception of bonds portrayed. It proposes the term ‘buddy banter’ as a means to illustrate the presentation of close celebrity friendships in a multi-gender, group environment. Analysis revealed banter to be a useful means of attracting audience attention, while audience interpretation of celebrity dynamics favoured the reading of close cross-gender friendships as heterosexual couples.